Orthodontic treatment of a severe unilateral open bite and crossbite, by palatal appliance with monolateral screw (by Veltri). A case report - Perović, Tatjana; Aleksić, Ilija; Blažej, Zorica (Vojnosanitetski pregled, 2020)
Introduction. An appliance according to Veltri is a kind of palatal constructions, which in our region rarely used. Appeared as a logical consequence of the evolution of appliances for rapid palatal separation. Indicated primarily at distalisation upper molars. However, his good qualities allow the use of this device with other orthodontic problems.Case report. The aim is overview of the therapy fourteen-boys with asymmetry of the upper dental arch and unilaterally open and crossbite, using the appliance according to Veltri. The plan of therapy is provided to, primarily, correction of upper arch asymmetry by using appliance according to Veltri. Then to extract the lower first premolars and application of upper and lower fixed appliance for leveling the upper and lower dental arch, normalization overjet and the depth of overlap. The total duration of therapy was two years ago.Conclusion. Shown a combined camouflage therapy achieved a satisfactory result, regardless of the poor prognosis due to hyperdivergent growth.
Keywords: malocclusion; orthodontic appliance design; cephalometry; dental arch; treatment outcome.